2014
DOI: 10.1590/abd1806-4841.20142633
|View full text |Cite
|
Sign up to set email alerts
|

Nail psoriasis: a review of the literature

Abstract: Nails are considered epidermal appendages, and as such, are commonly affected in patients with psoriasis, 80% of whom are likely to develop nail psoriasis as a result of their condition. Two patterns of nail disorders have been shown to be caused by psoriasis. Nail matrix involvement can result in features such as leukonychia, pitting (punctures or cupuliform depressions), red spots in the lunula and crumbling. Nail bed involvement, on the other hand, can cause onycholysis, salmon or oil-drop patches, subungua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 42 publications
3
42
0
8
Order By: Relevance
“…The same observations were communicated by Essayed et al [29]. According to literature data, the thickness of the nail bed could be a morphologic marker for a subclinical nail involvement and a good parameter for the evaluation of the therapeutic eicacy [46].…”
Section: Resultssupporting
confidence: 52%
“…The same observations were communicated by Essayed et al [29]. According to literature data, the thickness of the nail bed could be a morphologic marker for a subclinical nail involvement and a good parameter for the evaluation of the therapeutic eicacy [46].…”
Section: Resultssupporting
confidence: 52%
“…Despite new molecules discovered in the last two decades many patients remain untreated, do not respond or lose response, or suffer from treatment‐related side effects; in particular psoriasis affecting the nails, scalp, and palms can often be difficult to treat (Gisondi et al, ). Nail psoriasis affects 10–90% of adult patients with plaque psoriasis, and has been reported in 63–83% of patients with psoriatic arthritis (PsA; Schons et al, ). Nail involvement may place a significant burden on patients as a result of functional impairment of manual dexterity, pain, and psychosocial embarrassment.…”
Section: Introductionmentioning
confidence: 99%
“…Van Laborde et al have shown that there is an 80% to 90% lifetime incidence of nail involvement in psoriatic patients [4]. The presence of nail involvement of psoriasis is associated with an increase in patient-reported pain complaints, functional impairment and social burden, resulting in a significant restriction of daily activities and quality of life as well as resistance to treatment [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%